Exploring the Impact of Artificial Intelligence on Consumer Behavior - Marwan Effendi; Alfi Fuadah; Mar'atush Sholihah (Lembaga Pengembangan Kinerja Dosen, 2025)
This study explores the impact of artificial intelligence (AI) on consumer behavior within digital commerce environments. The rapid integration of AI technologies such as personalized recommendations, automated customer service, and algorithmic decision making has reshaped how consumers interact with brands, influencing both psychological and behavioral outcomes. However, existing models like the Technology Acceptance Model (TAM) and Unified Theory of Acceptance and Use of Technology (UTAUT) often overlook emotional, trust related, and contextual dynamics in AI mediated interactions. This research aims to fill these gaps by applying a qualitative, systematic literature review methodology, guided by the Stimulus Organism Response (S-O-R) framework. Through reflexive thematic analysis of academic sources published between 2020 and 2025, four key constructs were identified: AI personalization, consumer trust, emotional response, and technological readiness. Findings indicate that while AI driven personalization enhances engagement and purchase intention, its effectiveness depends on trust, emotional comfort, and individual readiness to adopt new technologies. The study proposes a conceptual model integrating these factors, highlighting that AI’s success in shaping consumer behavior hinges on ethical design, transparency, and psychological alignment with user traits. These insights extend current theoretical understanding and offer practical implications for marketers and system designers. The study concludes that a consumer centric, emotionally intelligent approach to AI design is essential to achieving sustainable digital engagement and loyalty.